2018
DOI: 10.1108/ecam-06-2017-0106
|View full text |Cite
|
Sign up to set email alerts
|

Survival strategies of built environment organisations in a challenging economy

Abstract: Purpose The economic downturn in Nigeria calls for the need to appraise the survival strategies being adopted by organisations within the built environment, as it plays a major role in the development of every nation. The purpose of this paper is, therefore, to appraise the survival strategies of organisations within the built environment, with a view to showcasing these strategies to ensure continuous survival of organisations within the industry. Design/methodology/approach The study adopted a survey appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 30 publications
1
34
0
1
Order By: Relevance
“…However, with the exception of studies by Olatunji et al (2017) and Oke et al (2018), limited studies have focussed on the bidding challenges facing the indigenous contractors. Instead, other scholars have focussed on survival practices of indigenous construction firms (ICF) Challenges impacting bid decision (Ogbu, 2018;Aghimien et al, 2018); and critical success factors against competitive advantages of ICF (Somiah et al, 2019). Table 1 presents a summary of selected reviewed studies that have explored challenges influencing the bid decision-making practices.…”
Section: Challenges Impacting the Bid Decision Practicesmentioning
confidence: 99%
“…However, with the exception of studies by Olatunji et al (2017) and Oke et al (2018), limited studies have focussed on the bidding challenges facing the indigenous contractors. Instead, other scholars have focussed on survival practices of indigenous construction firms (ICF) Challenges impacting bid decision (Ogbu, 2018;Aghimien et al, 2018); and critical success factors against competitive advantages of ICF (Somiah et al, 2019). Table 1 presents a summary of selected reviewed studies that have explored challenges influencing the bid decision-making practices.…”
Section: Challenges Impacting the Bid Decision Practicesmentioning
confidence: 99%
“…This strategy of survival can be seen as a means of diversifying into a different method of contracting which originally these set of contractors might not be used to. Past research has shown that most diversified construction firms in Korea, the UK and Singapore tend to diversify into construction-related services, and considerable success has been experienced by these firms (Cho, 2003;Langford and Male, 2001;Ofori and Chan, 2000) In Nigeria, Aghimien et al (2018) also noted that construction organisations are beginning to adopt this strategy of diversifying into other construction-related activities in a bid to survive the striving economy and competitive environment in which they find themselves. This was also in confirmation of Abu Bakar et al (2011) observation of diversification being a common survival strategy adopted by organisations in Malaysia during the harsh economy.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Unfortunately, Nigeria is confronted with these issues because of its historical economic instability (Abioye 2017;Aghimien et al, 2018). Bello-Schünemann and Porter (2017) noted that economic growth in Nigeria is influenced by substantive deficit in the country's basic physical infrastructure.…”
Section: Challenges Of Smart City Developmentmentioning
confidence: 99%